Bioremediation of Persistent Organic Pollutant—Oxybenzone with Pleurotus djamor - Kryczyk-Poprawa, Agata; Baran, Wojciech; Sułkowska-Ziaja, Katarzyna; Kała, Katarzyna; Adamek, Ewa; Król, Małgorzata; Sánchez-Hidalgo, Adrián; Muszyńska, Bożena (Applied sciences, 2025)
Oxybenzone, a common sunscreen ingredient, has been widely detected in various environmental matrices, posing significant ecological and health risks. The present study demonstrates, for the first time, the capacity of Pleurotus djamor to degrade oxybenzone in in vitro cultures. After 14 days of mycelial incubation, oxybenzone concentrations in the medium decreased from 25 mg to 1.5394 ± 0.095 mg. The final amount of oxybenzone in the mycelium after lyophilization was 6.2067 ± 0.2459 mg. Furthermore, oxybenzone addition significantly reduced biomass growth from 2.510 ± 0.6230 g to 1.4697 ± 0.0465 g. The transformation products in the dry mycelium and medium were assessed and identified using UPLC-Q-tof based on monoisotopic molecular mass and fragmentation spectra. In processes initiated by P. djamor, mainly acylated derivatives of oxybenzone were formed. Additionally, compounds with thiol and amino groups were identified. Alterations in antioxidant profiles (L-tryptophan, 6-methyl-D,L-tryptophan, p-hydroxybenzoic acid, ergosterol, lovastatin, L-phenylalanine, and ergothioneine) in response to oxybenzone exposure were observed. Our findings reveal significant changes in the antioxidant levels and biomass growth inhibition, underscoring the potential toxicological risks associated with oxybenzone. The observed reduction in oxybenzone concentration highlights the potential of P. djamor as an effective and environmentally friendly strategy for mitigating this pollutant.